The Role of Notaries In Providing Legal Certainty of Investment In Indonesia - Wetria Fauzi; Zulkifli (Jurnal Sakato Ekasakti Law Review, 2026)
Every country is competing to create a conducive investment climate. However, the high investment potential does not automatically make Indonesia a primary destination for investors. One factor that investors pay primary attention to when conducting investment activities is legal certainty. Investors need assurance that their rights will be protected by law. The government's efforts to create legal certainty in investment are realized through the establishment of various laws and regulations, one of which is Law Number 25 of 2007 concerning Investment. This law provides the legal basis for investment activities in Indonesia, both domestic and foreign investment. Furthermore, the government also reformed regulations through Law Number 6 of 2023 concerning the Establishment of the Job Creation Law, which is a law aimed at increasing the ease of doing business and improving the national investment climate. However, in practice, the role of notaries in realizing legal certainty in investigations still faces various obstacles and challenges. One of the problems that occurs is the rapid changes in investigation regulations, which give rise to uncertainty in business law practices. Furthermore, there is still overlapping regulations between agencies, causing the investigation process to become more complicated and complicated.